trig
posted by Rick .
please simplify
sin (7pi/6 x) + cos (2pi +x)

Use the formulas for sin (A  B) and cos (A + B)
I can tell you right away that cos (2 pi + x) = cos x
Respond to this Question
Similar Questions

trig
Reduce the following to the sine or cosine of one angle: (i) sin145*cos75  cos145*sin75 (ii) cos35*cos15  sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b)  sin(a)sin)(b) (1)The quantity … 
Trig
Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < 2pi Find: sin (v + u) cos (v  u) tan (v + u) First compute or list the cosine and sine of both u and v. Then use the combination rules sin (v + u) = sin u cos … 
algebra
Can someone please help me do this problem? 
math
Eliminate the parameter (What does that mean? 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 … 
Precal
I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A + cos A) ) = 1  sin A cos A note that all the trig terms are closed right after there A's example sin A cos A = sin (A) cos (A) I wrote it out like this 0 =  … 
trig 26
simplify to a constant or trig func. 1. sec ²utan ²u/cos ²v+sin ²v change expression to only sines and cosines. then to a basic trig function. 2. sin(theta)  tan(theta)*cos(theta)+ cos(pi/2  theta) 3. (sec y  tan y)(sec y + … 
Math
use Demoivre's Theorem to find the indicated power of the complex number. Express the result in standard form. (2+2i)^6 a=2 b=2 n=6 r=sqrt 2^2 + 2^2 = sqrt8 Q=7pi/4 (sqrt8)^6 = 512 512(cos 6/1 x 7pi/4) + i sin 6 x 7pi/4 512 (cos 21pi/2) … 
Math
use Demoivre's Theorem to find the indicated power of the complex number. Express the result in standard form. (2+2i)^6 a=2 b=2 n=6 r=sqrt 2^2 + 2^2 = sqrt8 Q=7pi/4 (sqrt8)^6 = 512 512(cos 6/1 x 7pi/4) + i sin 6 x 7pi/4 512 (cos 21pi/2) … 
Math
3. find the four angles that define the fourth root of z1=1+ sqrt3*i z = 2 * (1/2 + i * sqrt(3)/2) z = 2 * (cos(pi/3 + 2pi * k) + i * sin(pi/3 + 2pi * k)) z = 2 * (cos((pi/3) * (1 + 6k)) + i * sin((pi/3) * (1 + 6k))) z^(1/4) = 2^(1/4) …